Effectiveness of Resilience Training to Reduce Caregiver Burden in Family Caregivers of Children with Cancer - Ananda Imanuela Nainggolan; Tri Ratna Sari; Hartanti Hartanti (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2022)
Cancer patients generally have families who provide some level of care. The family or family caregiver has a big task and role in serving the needs of the patient, both physically and psychologically. The role and level of these responsibilities can lead to a high burden or pressure felt by the family caregiver, which is called the caregiver burden. This training targets resilience as a variable that can reduce the caregiver burden of family caregivers. The research design is a one group pretest and posttest experimental design. The number of participants who took part in the entire training process was four people. The results of the different test showed a significance of 0.144 (p > 0.05), which means that there was no significant difference in the caregiver burden level after the training. Several factors that influence the failure of resilience training to reduce the level of caregiver burden from family caregivers are the existence of a social desirability bias towards measuring instruments, differences in the educational background of participants, and the short training implementation. Pasien kanker pada umumnya memiliki keluarga yang memberikan perawatan pada tingkat tertentu. Keluarga atau family caregiver memiliki tugas dan peran yang besar dalam melayani kebutuhan pasien, baik secara fisik maupun psikologis. Peran dan besarnya tanggung jawab tersebut dapat menimbulkan tingginya beban atau tekanan yang dirasakan oleh family caregiver yang disebut caregiver burden. Pelatihan yang dilakukan ini menyasar resiliensi sebagai variabel yang dapat mengurangi caregiver burden dari family caregiver. Desain penelitian ini adalah one group pretest and posttest experimental design. Jumlah peserta yang mengikuti keseluruhan proses pelatihan yaitu sebanyak 4 orang. Hasil uji beda menunjukkan signifikansi 0.144 (p > 0.05) yang berarti tidak ada perbedaan tingkat caregiver burden yang signifikan setelah dilakukan pelatihan. Beberapa faktor yang memengaruhi tidak berhasilnya pelatihan relisiensi untuk mengurangi tingkat caregiver burden dari family caregiver yaitu adanya social desirability bias terhadap alat ukur, perbedaan latar belakang pendidikan peserta, dan pelaksanaan pelatihan yang singkat.